The spirit of modern sacral architecture - Zuba, Karolina (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Sacral architecture, due to its special function, is able to tremendously influence the society. Being a phenomenon for ages, it has undergone many changes alike the church liturgy, which to some extent impacts the church architecture. In the modern sacral architecture it is possible to distinguish two main tendencies in creating objects of temples. The first one is entirely modest – simplicity of form and interior. The second tendency, which may be described as the opposite of the former, presents monumentalism usually connected with rich symbolism. Modern temples also show references to historical forms. Another factor which may influence the form and function of the sacral object is the religious beliefs of its author.